Magnification and Correction of the Acolyte Effect: Initial Benefits and Ex Post Settling up in NFL Coaching Careers - Kilduff, Martin; Crossland, Craig; Tsai, Wenpin; Bowers, Matthew T. (Academy of Management Journal, 2016)
What are the long-term consequences of initially beneficial high-reputation workplace ties? Under uncertainty, acolytes (i.e., subordinates with work connections to high-reputation industry leaders) are likely to benefit in terms of signaling fitness for promotion in the external job market. Analysis of promotion outcomes of coaches in the National Football League over 31 years showed that the acolyte effect was reduced for individuals for whom uncertainty was lowest (acolytes with considerable industry experience or high centrality in the co-worker industry network). There was no support for either a knowledge-transfer or an intrinsic-quality explanation for why acolytes initially gained advantage. Rather, evidence supported the idea that ties to high-reputation leaders were somewhat randomly distributed so that acolytes faced ex post settling-up consequences after their promotions: i.e., fewer further promotions or lateral moves, and more demotions. Thus, acolytes initially benefited from loose linkages between their unobservable quality and signals offered by their industry-leader ties, but also suffered as the unreliability of social network signals became evident. The results suggest that a competitive job market may exhibit self-correction over time. We offer countervailing theory and evidence to the prevailing view that high-reputation third-party endorsements perpetuate a rich-get-richer social structure that is resistant to performance outcomes.